Elementos da ética sexual Tomista - Lopes, Jailson Silva (2011)
This dissertation aims to present a elementar vision of thomistic thought about human sexuality from knowledges of vices and virtues. Introduce the notion of vice as otherwise to human nature and seek its etymological meaning, approaching with the neotestamentary perspective of sin and malice. This notion is based in aristotelian and augustinian notion, used by Thomas Aquinas. Also present two virtues inside of the christian thought about the sexuality. They are temperance and chastity. The temperance is a virtue that orders the pleasures of tact, and regulates the chastity. Finally, we show that is possible in thomistic thought admit the legitimacy of sexual pleasure and also the natural necessity in relations, and this relations just can be designed inside of legitimate marriage